Pengaruh Kualitas Makanan Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Di Moka Restoran Pada Astagina Resort Villa And Spa, Legian Bali - Hanung, Yuliana Devila; Sutapa, I Ketut; Dewi, Desak Made Purnama (Jurnal Mosaik Hospitaliti, 2023)
In businesses engaged in the service sector, customer satisfaction is the most important thing to maintain, which will certainly have a very good impact on the business going forward. This is the main background of the research entitled "The Influence of Food Quality and Service Quality on Customer Satisfaction at Moka Restaurant at Astagina Resort Villa and Spa, Legian Bali". The purpose of this study was to determine the partial and simultaneous effect of food quality and service quality on customer satisfaction, to find out how much influence food quality and service quality have on customer satisfaction, and to find out which variables have more influence on customer satisfaction at Moka Restaurant in Astagina Resort Villa and Spa, Legian Bali. This study uses a type of quantitative research, the type of data used is quantitative and qualitative. Data collection techniques used in this study were observation, interviews, documentation and questionnaires. There are 95 samples used in this study. The data analysis technique used in this research is quantitative descriptive analysis with the help of the SPSS tool. The results showed that food quality had a positive effect on customer satisfaction. Service quality has a positive effect on customer satisfaction. Food quality and service quality have a simultaneous effect on customer satisfaction. Suggestions for Moka Restaurant to pay more attention to food quality, maintain service quality and customer satisfaction. And this research is expected to be a literature review in further research.